DAMPAK PANDEMI COVID-19 TERHADAP KEGIATAN KEAGAMAAN DI VIHĀRA DHAMMADĪPA SURABAYA - Shehilla Diana Lawrenza (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
The background of the research problem is the extent to which changes before and during the Covid-19 pandemic occurred in religious activities. The Covid-19 pandemic that occurred in Indonesia resulted in limited activities. The spread of the virus at the world level forced the Government of the Republic of Indonesia to carry out policies. The purpose of the study was to determine the impact of the Covid-19 pandemic on religious activities at Vihāra Dhammadīpa Surabaya. The research was conducted using descriptive qualitative methods. The research focused on routine religious activities carried out offline and then replaced with online. Sources of research data obtained from the results of interviews conducted with 6 informants. Supported data in the form of literature, previous research studies, library books, photos and online media sources. The data collection techniques were obtained through observation, interviews, and documentation techniques. The results of this study indicate that the activities at the Vihāra have decreased due to the Covid-19 pandemic. People's perspective on religion has undergone drastic changes such as spiritual, psychological and changes in time and place of worship.